PRE-SLAUGHTER STRESS ESTIMATION BY FOURIER TRANSFORM INFRARED SPECTROSCOPY ANALYSIS - Widiyanto, S.; Widiyono, I.; Purwono, P.; Astuti, P. (Diponegoro University, 2014)
The objective of the study was to analyze the potential of fourier transform infrared (FTIR) asstress estimation instrument through measurement of catecholamine (CA) and cortisol (CO) levels byinvasive and non-invasive methods. Twelve heads of Ongole grade (PO) cow from slaughterhouse wereused in this study. Twenty four urine samples of pre-slaughter and slaughtering were collected toevaluate the CA and CO levels by ELISA method and Fourier Transform Infrared (FTIR). Data of CAand CO levels were statistically analyzed to determine the difference between pre slaughter andslaughter conditions. FTIR spectra were analyzed using chemo-metrics software. The results showedthat the levels of urinary cortisol were 2.12±1.68 ng/dl of pre-slaughter and 7.58±3.89 ng/dl ofslaughtered and the levels of urinary catecholamine in pre slaughter and slaughter were 3.07±2.05 and4.15±2.68 ng/dl respectively. The results showed a correlation between the FTIR spectra and the resultsof ELISA analysis. FTIR spectrums were distributed in different quadrants, this was caused bydifferences of CA and CO levels between pre-slaughter and slaughtered. It can be concluded that FTIRcan be supposed to analyze the status of stress in animals, especially in cattle.